Plant diversity effects on herbivory are related to soil biodiversity and plant chemistry. (28th November 2022) - Ristok, Christian; Weinhold, Alexander; Ciobanu, Marcel; Poeschl, Yvonne; Roscher, Christiane; Vergara, Fredd; Eisenhauer, Nico; van Dam, Nicole M.
Abstract: Insect herbivory is a key process in ecosystem functioning. While theory predicts that plant diversity modulates herbivory, the mechanistic links remain unclear. We postulated that the plant metabolome mechanistically links plant diversity and herbivory. In late summer and in spring, we assessed individual plant above‐ground herbivory rates and metabolomes of seven plant species in experimental plant communities varying in plant species diversity and resource acquisition strategies. In the same communities, we also measured plant individual biomass as well as soil microbial and nematode community composition. Herbivory rates decreased with increasing plant species richness. Path modelling revealed that plant species richness and community resource acquisition strategy correlated with soil community composition. In particular, changes in nematode community composition were related to plant metabolome composition and thereby herbivory rates. Synthesis . These results suggest that soil community composition plays an important role in reducing herbivory rates with increasing plant diversity by changing plant metabolomes. Abstract : A new mechanistic framework for future experimental research on plant–soil‐herbivore interactions. We assessed foliar insect herbivory and metabolomes of seven functionally dissimilar plant species as well as associated soil biota in a long‐term, large‐scale grassland biodiversity experiment. We discovered that plant individual herbivory decreased with increasing plant species richness related to changes in nematode community composition and plant metabolome composition.